Pengembangan Media Game Edukasi Wordwall Sebagai Media Pembelajaran Bahasa Indonesia Siswa Sekolah Dasar - Hanny Pramitha Putri; Dede Rizki Saepullah; Raka Ismaya; Oktavia Tri Rahmawati; Zahra Salsabil (STKIP Subang, 2026)
The use of instructional media in elementary schools faces several challenges, including overly formal learning materials, limited classroom interaction, and students' low interest in the learning process. This study employed a Research and Development (R&D) approach to develop an interactive educational game in the form of a Wordwall-based interactive PowerPoint to support first-grade students in learning the Indonesian language. The development process followed the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected using validation sheets, student response questionnaires, and student activity observation sheets. The research participants were three-grade students at SD Negeri Cilenggang 02 Tangerang Selatan. The findings indicate that the developed Wordwall-based educational game integrated into an interactive PowerPoint is valid, practical, and effective as a learning medium. The material validation achieved a feasibility score of 87.4%, while media validation reached 87%, indicating that the product is highly feasible for classroom use. The limited and field trials demonstrated a practicality score of 95%, confirming that the media is easy to use in the learning process. Furthermore, the effectiveness evaluation showed a student activity score of 89.5%, indicating that the media successfully promoted active student participation during learning. Therefore, the Wordwall-based educational game developed through interactive PowerPoint is considered an appropriate and effective instructional medium for teaching the Indonesian language in elementary schools.